Incidence of Mumps in Anbar province, West of Iraq during the Period 2009-2018 - Mothana Ali Khalil1 , Hekmat Ahmed Owaid2 , Shehab Ahmed Lafi3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Mumps (infectious parotid gland) is an infectious viral disease mainly affects children andadolescents characterized by enlargement of parotid and salivary glands, other epithelial tissues may beaffected, in some cases it is accompanied by serious complications. In recent years many mumps cases inAnbar province have appeared in people who have been vaccinated with Mumps vaccine and for reasonsthat are not clearObjective: To Show the annual mumps incidence with age groups and sex for those affected in AnbarprovinceMethods: A Descriptive cross-sectional study of the electronic archives of mumps patients who wereimmediately registered in Anbar Governorate hospitals, during the period from 2009 to 2018. Thequestionnaires regarding year of infection, gender, and age of mumps patients included in the study. Mumpsincidence has been calculated through dividing the number of annual cases of infection by population sizemultiplied by 100,000. SPSS software version 24 were used for data analysis.Results: Of 2924 Mumps patients registered at Anbar province hospitals, 1715 (58.7%) were males with 12.1± 4 years mean age . The incidence rates of Mumps in 2009, 2010, 2011, 2012, 2013, 2014, 2015,2016,2017& 2018 were (0.50, 0.20, 0.70, 0.80, 1.70, 0.00, 0.00, 7.20, 97.90& 59.00) / 100,000 respectively withstatistically variance among males & females; p value = 0.000 & annual incidence ratio was 21.00 / 100,000.Annual Mumps incidence ratio from 2009-2018 confirmed one peak in 2017-2018 & a rare 2009-2016,Majority of them were in the age group 5 to14 years old.Conclusion: Mumps incidence had been increase during the last 2 years mainly in the age group 5 to14years old with a marked increase incidence in male in Anbar province, Iraq